PENGEMBANGAN BAHAN AJAR EKONOMI KELAS XII SEMESTER 1 DI SMA - Sutrisno, Sumin; Murbojono, Rahmat; Suratno, Suratno (Program Magister Teknologi Pendidikan Universitas Jambi, 2012)
This research aims to develop teaching materials economic class XII semester I in high school. Content of teaching materials designed using Kurikulum Tingkat Satuan Pendidikan high school. With Instructional Materials efective and interested hoped can be need of Insructionasl Materials in SMAN I Sarolangun. The development model using Dick and Carey (1994) model. The development prosedure which is conducted follows Dick and Carey design, the prosedures are: (1) determining the instruction objectives, (2) conducting instruction analysis, (3) identificating the studentsâ€™ prior knowledge and characteristics, (4) formulating spesific objectives, (5) developing criteria-determined assessment item, (6) developing the formatif evalvation, and (9) revising the instruction, (10) evaluation of summative. The result overall, showed the teaching material is catagorized â€œwellâ€. According to the instructional design expect, this teaching material is â€œwell / appropriate / interesting â€œ, so it is appropriate to be used as the teaching aterial in high school. Meanwhile, the instructional content expert gave assessment â€œvery wellâ€ for the development of the teaching material. The teaching material is developed by concerning the available prosedures and criterion. Teacher and students gave positif assessment to this development of teaching material on the field assessment. Generaly. Based on the analysis, both the expert validity and the field assessment showed, that the quality of the teaching material economic class XII semester 1 is â€œverywellâ€. So, it is suggested, that the product of this development can be used as the teaching material at educational unit of High School. Keyword: Subject Economic, Class XII High School, and Development Model.